A short-term cooling of root-zone temperature increases bioactive compounds in baby leaf Amaranthus tricolor L. - Wittayathanarattana, Takon; Wanichananan, Praderm; Supaibulwatana, Kanyaratt; Goto, Eiji (Frontiers in Plant Science, 2022)
Leafy vegetables that are offered as seedling leaves with petioles are referred to as baby-leaf vegetables. One of the most nutritious baby-leaf, amaranth (Amaranthus tricolor L.), contains several bioactive compounds and nutrients. Here, we investigated the growth and quality of baby-leaf amaranth using a variety of short-term cooling root-zone temperatures (RZT) (5, 10, 15, and 20 °C), periods (1, 3, 5, and 7 days), and combinations thereof. We observed that exposing amaranth seedlings to RZT treatments at 5 °C and 10 °C for 1 to 3 days increased the antioxidant capacity and the concentration of bioactive compounds, such as betalain, anthocyanin, phenolic, flavonoid, and ascorbic acid; however, extending the treatment period to 7 days decreased these and adversely affected growth. For RZT treatments at 20 °C, leaves photosynthetic pigments, bioactive compounds, nutrients, and antioxidant capacity increased gradually as the treatment period was extended to 7 days. The combination of RZT treatments at 5 °C and 10 °C for one day preceded or followed by an RZT treatment at 20 °C for two days had varied effects on the growth and quality of amaranth leaves. After one day of RZT at 5 °C followed by 2 days of RZT at 20 °C, the highest concentration of bioactive compounds, nutrients, and antioxidant capacity was observed, and growth was not impaired. The short-term cooling RZTs under controlled environments was proven to be an adequate condition to improve target bioactive compounds in amaranth baby-leaf without causing leaf abnormality or impairing growth.